SELERA KONSUMEN DALAM PEMBELIAN “ALMOND CRISPY” DI TOKO WISATA RASA JEMURSARI SURABAYA - Kusuma, Andi; Nugroho, Sigit Dwi; Parsudi, Setyo (Berkala Ilmiah AGRIDEVINA, 2017)
Culinary and snack business in Indonesia still has a pretty bright prospect. In the last fiveyears, Almond Crispy becomes teenagers prima donna which can be seen in shoppingmalls and several shops in Surabaya public area. Almost everyday, Wisata Rasa shop inJemursari Surabaya is full of visitors especially for visitors who buy Almond Crispyproduct. This research was conducted to identify consumer characteristic of AlmondCrispy in Wisata Rasa shop in Jemursari Surabaya for purchasing decision and toanalyze consumer taste for product attribute of Almond Crispy which was purchased inWisata Rasa shop in Jemursari Surabaya for purchasing decision. Consumercharacteristic of Almond Crispy in Wisata Rasa Jemursari Surabaya was dominated byadult age around 26 -45 years old. Almond Crispy consumer from Wisata Rasa JemursariSurabaya was dominated by women with education level was undergraduate and wasworking as a private employee with income per month was more than Rp 4.500.000/eachmonth. Product attribute which was noticed and recognized by consumer who boughtAlmond Crispy in Wisata Rasa shop Jemursari Surabaya consisted of brand, taste,texture, and price. Price and taste has the highest consumer attitude value. AlmondCrispy taste was considered delicious by consumer with an affordable price so that itcreated aggresiveness of product attribute and attracted consumer, both existing and newconsumer, to keep visiting this shop on their purchasing decision.